(untitled) (Web of Technology: Multidimensional Research Journal, 2025)
This article examines the rational use and conservation of aquatic bioresources under the conditions of climate change, focusing on ecological, technological, and socio-economic dimensions. The study highlights the growing threats posed by global warming, changing hydrological regimes, and anthropogenic pressures, which undermine the stability of aquatic ecosystems and reduce the availability of fishery and aquaculture resources. Emphasis is placed on the development of sustainable aquaculture systems, the introduction of ecosystem-based management practices, and the application of modern monitoring technologies to preserve biodiversity. The research also considers the role of scientific collaboration, policy frameworks, and community participation in ensuring effective conservation strategies. The findings suggest that the rational use and conservation of aquatic bioresources in the context of climate change require comprehensive approaches that integrate ecological balance, technological innovation, and socio-economic sustainability.